Comprehensive characterization of tobacco-induced changes in enamel surface topography - Tamanna Kaur; Ramya Ramadoss; Nitya Krishnasamy; Sandhya Sundar; Suganya Panneer Selvam; Hema Shree K (Journal of Oral Biology and Craniofacial Research, 2025)
Introduction: Enamel translucency, essential for the aesthetic appeal of teeth, is primarily determined by its thickness, quality, and refractive index. Several factors, including age, genetics, diet, oral hygiene practices, fluoride exposure, and acidic challenges, can influence enamel translucency. Tobacco use, in particular, leads to significant alterations in enamel appearance by penetrating its micropores, causing yellowing and browning. Prolonged exposure to tobacco results in demineralization, increasing enamel porosity and reducing its translucency. Over time, this exposure leads to permanent discoloration and structural degradation, rendering teeth dull and opaque. To assess these changes, various methods such as visual examinations, digital photography, spectrophotometry, stylus profilometry, and atomic force microscopy (AFM) are utilized. Materials and methods: This study analyzed human enamel samples, including one unstained sample (Grade 0) and three tobacco-stained samples (Grades 1–3) according to Modified Lobene Stain Index (MLSI), to investigate the impact of tobacco exposure on enamel structure. The samples were thoroughly cleaned and dried to ensure accurate results. High-resolution AFM imaging was employed to assess surface roughness, porosity, and microstructural changes induced by tobacco staining. A stylus profilometer was used to trace the surface topography, providing detailed measurements of surface irregularities. Additionally, a spectrophotometer was utilized to evaluate the optical properties of the enamel, focusing on changes in translucency and light absorption due to tobacco exposure. Results: AFM analysis revealed a clear progression of enamel surface roughness from Grade 0 to Grade 3. The Sa and Sq values increased significantly with the severity of tobacco staining, indicating greater surface degradation. The stylus profilometer data corroborated these findings, with rising Ra values as the degree of staining intensified, highlighting the topographical alterations caused by tobacco exposure. Spectrophotometric analysis further demonstrated a decrease in enamel reflectance and an increase in light absorption from mild to severe staining, underscoring the detrimental optical effects of tobacco on enamel. Conclusion: The combined use of AFM, stylus profilometry, and spectrophotometry provided a comprehensive assessment of the impact of tobacco staining on enamel translucency and surface roughness. The findings show that as staining severity increases, enamel translucency diminishes, and surface roughness worsens. These alterations not only affect the aesthetic appearance of teeth but also have potential implications for enamel functionality and long-term oral health.